Status and challenges for molecular solar thermal energy storage system based devices. (21st June 2022) - Wang, Zhihang; Hölzel, Helen; Moth-Poulsen, Kasper
Abstract : Molecular solar thermal energy storage systems (MOST) can store solar power via valence photoisomerization in molecular photoswitches. MOST concept based devices offer emission-free solar energy storage and release on-demand. Abstract : Molecular solar thermal energy storage systems (MOST) offer emission-free energy storage where solar power is stored via valence isomerization in molecular photoswitches. These photoswitchable molecules can later release the stored energy as heat on-demand. Such systems are emerging in recent years as a vibrant research field that is rapidly transitioning from basic research to applications. Since a major part of the attention is focused on molecular design and engineering, MOST-based device development has not been systematically summarized and introduced to a broad audience. This tutorial review will discuss the most commonly used and developed devices from a chemical engineering point of view. It is expected that future developers of MOST technology could be inspired by the existing devices, keeping in mind the summarized essential practical challenges towards large-scale implementations and more innovative applications.